Gambaran Komunikasi Antarbudaya Dalam Pasangan Pernikahan Beda Etnis Batak-Nias Di Desa Hutagodang Kecamatan Batang Toru Kabupaten Tapanuli Selatan - Devi Asna Sari Panggabean; Albiner Siagian; Roida Lumbantobing; Hanna Dewi Aritonang; Martua Sihaloho (Jurnal Mahasiswa Kreatif, 2023)
The research background is related to inter-ethnic marriages carried out by couples with different linguistic and cultural backgrounds, namely the Batak and Nias Adanva ethnicities. Differences in different linguistic and cultural backgrounds result in differences in interpreting and understanding the message or information conveyed, this can giving rise to misunderstandings. This research was conducted in Hutagodang Village, Kec. Batang Toru. South Tapanuli Regency.The main problem in this research is the description of intercultural communication and communication barriers between inter-ethnic marriage couples in Hutagodang Village. This research aims to find out and explain how intercultural communication in inter-ethnic marriage couples and what communication barriers occur in inter-ethnic marriage couples.